TRPV4 calcium entry and surface expression attenuated by inhibition of myosin light chain kinase in rat pulmonary microvascular endothelial cells. Issue 5 (27th October 2013) - Parker, James C.; Hashizumi, Masahiro; Kelly, Sarah V.; Francis, Michael; Mouner, Marc; Meyer, Angela L.; Townsley, Mary I.; Wu, Songwei; Cioffi, Donna L.; Taylor, Mark S.
Abstract: In previous studies, blockade or gene deletion of either myosin light chain kinase (MLCK) or the mechanogated transient receptor potential vanilloid 4 (TRPV4) channel attenuated mechanical lung injury. To determine their effects on calcium entry, rat pulmonary microvascular endothelial cells (RPMVEC) were labeled with fluo‐4 and calcium entry initiated with the TRPV4 agonist, 4α‐phorbol 12, 13‐didecanoate (4αPDD). Mean calcium transients peaked at ~25 sec and persisted ~500 sec. The 4αPDD response was essentially abolished in calcium‐free media, or after pretreatment with the MLCK inhibitor, ML‐7. ML‐7 also attenuated the 4αPDD‐induced inward calcium current measured directly using whole‐cell patch clamp. Pretreatment with dynasore, an inhibitor of dynamin produced an initial calcium transient followed by a 4αPDD transient of unchanged peak intensity. Automated averaging of areas under the curve (AUC) of calcium transients in individual cells indicated total calcium activity with a relationship between treatment groups of ML‐7 + 4αPDD < 4αPDD only < dynasore + 4αPDD. Measurement of biotinylated surface TRPV4 protein indicated a significant reduction after ML‐7 pretreatment, but no significant change with dynasore treatment. RPMVEC monolayer electrical resistances were decreased by only 3% with 10 μmol/L 4αPDD and the response was dose‐related. Dynasore alone produced a 29% decrease in resistance, but neither ML‐7 nor dynasore affected the subsequent 4αPDD resistance response. These studies suggest that MLCK may inhibit mechanogated calcium responses through reduced surface expression of stretch activated TRPV4 channels in the plasma membrane. Abstract : e00121 Abstract : Fluorescent micrograph showing colocalization of transient receptor potential vanilloid 4 (TRPV4) and focal adhesion kinase (FAK) in basilar region of rat pulmonary microvascular endothelial cells.